Financial Factors and Dividend Policy: Influencing Stock Prices: Dampak Likuiditas, Leverage, Profitabilitas, dan Ukuran Perusahaan terhadap Harga Saham: Peran Mediasi Kebijakan Dividen - La'ikotun Nahdiyah; Imelda Dian Rahmawati (Academia Open, 2022)
This study investigates the relationship between liquidity, leverage, profitability, firm size, and stock prices, with dividend policy acting as a mediating variable. A purposive sampling method was employed, selecting 10 banking companies listed on the IDX during the period 2016-2019. Secondary data was utilized, and the PLS (Partial Least Square) 3.2 analysis method was applied. The findings reveal significant effects of liquidity, leverage, profitability, and firm size on stock prices. Furthermore, liquidity, leverage, and profitability exerted an influence on dividend policy, which in turn affected stock prices. Dividend policy was found to mediate the relationships between liquidity, leverage, profitability, firm size, and stock prices. These results contribute to the understanding of how various financial factors and dividend policy interplay in shaping stock prices. The findings have important implications for investors, financial managers, and policymakers in making informed decisions regarding stock market investments and dividend policy strategies. Highlights: The study examines the impact of liquidity, leverage, profitability, and firm size on stock prices. Dividend policy is analyzed as a mediating variable in the relationship between financial factors and stock prices. The findings demonstrate significant effects of liquidity, leverage, profitability, and firm size on stock prices, with dividend policy playing a crucial role in mediating these relationships. Keywords: Liquidity, Leverage, Profitability, Firm Size, Dividend Policy